Designers' guide to Eurocode 8 design of bridges for earthquake resistance, EN 1998-2 - Kolias, Basil (Designers' guides to the Eurocodes., 2012)
This guide focuses specifically on EN 1998-2 (Eurocode 8. Part 2 Bridges), the design standard for use in the seismic design of bridges in which horizontal seismic actions are mainly resisted through bending of the piers or at the abutments; however it can also be applied to the seismic design of cable-stayed and arched bridges.